The Effect of Job Satisfaction on Employee Performance Study at The Zuri Hotel, Pekanbaru - Zarini, Irma; Serly, Serly (Nexus Synergy: A Business Perspective, 2024)
The purpose of this study is to determine and analyze employee job satisfaction and performance and the effect of job satisfaction on employee performance at The Zuri Hotel Pekanbaru. The research method used is a descriptive and explanatory survey method with a population of employees of The Zuri Hotel Pekanbaru and a sample of 55 respondents using a data analysis method in the form of simple linear regression, namely the SPSS 20 data analysis tool. Then from the results of the study it was concluded that employee job satisfaction is in the high category and employee performance is also in the high category and job satisfaction has an effect on employee performance at The Zuri Hotel Pekanbaru. The coefficient of determination (R2) of job satisfaction on employee performance is 44.50% while employee performance is influenced by other variables not examined in this study is 55.50%.